THE NATURE OF MAGNETIC CHEMICALLY PECULIAR STARS PHENOMENON AND THE ORIGIN OF LITHIUM - Gopka, V. F.; Shavrina, A. V.; Yushchenko, A. V.; Yushchenko, V. A. (Одеські астрономічні публікації, 2012)
According to the modern theory of the evolution of chemical elements their origin seems understandable for most of the elements, from the lightest up to the heavy ones. For element with atomic number Z=3 (lithium) the situation is following: the physical processes and the possible mechanisms of lithium production in stars of different types and ages remain completely unidentified up to now. This paper is an attempt to explain the observed properties of lithium in the magnetic chemically peculiar (MCP) stars by the existence of a neutron star (NS) companion. It is supposed that MCP stars are binary systems with stable relativistic outflow of charged particles falling on the poles of MCP stars along the magnetic field lines (Gopka et al., 2010). The production of lithium is possible as a result of interaction of highly accelerated charged particle and the photosphere of MCP star. The location of lithium spots on the magnetic poles seems natural. The problem of lithium formation is directly connected to the problem of origin of MCP stars. The assumption of origin of double systems with presupernova is based on the observations of binary population in OB association Sco2 (Brown, 2001) is discussed. The distribution of primordial binary population clearly answers the question about the origin of systems with NS companions. The phenomenon of MCP stars with lithium production can be the key to he understanding of the origin of Li in other stellar objects. It is assumed that the formation of binaries with a primary star at the evolutionary stage of pre-supernova occurs in the areas of star formation due to the ambient matter accretion and the mass exchange between the stars of intermediate mass in binary systems. The explosion of a more massive companion as a type II supernova results in a qualitative change in binary system when a young star is accompanied by a neutron star. Such systems can be a lithium producers. An important aspect of his assumption is a clear understanding of the evolutionary status of young objects at the stage before the main-sequence, the progenitors of MCP stars, such as the Herbig AeBe stars. The observational data for Herbig AeBe stars (and for T Tauri stars with Herbig AeBe properties continuing in the region of stars with masses less than 2 Msun.) indicate the existence of young stars surrounded by accretion disks with typical outflow along the magnetic field lines of the disk. It was pointed by Grinin & Tambovtseva (2012) and now can be explained in the framework of our model of MCP stars (Gopka et al., 2010). On the other hand, the binary systems containing a NS companion and the detectable lithium, were really identified by Martin et al. (1994) and Rebolo et al. (1995).